2018
DOI: 10.1007/s00167-018-5239-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament repair with Independent Suture Tape Reinforcement: a case series with 2-year follow-up

Abstract: Purpose The treatment of acute anterior cruciate ligament (ACL) ruptures with a repair technique has recently regained interest. A novel ACL repair technique was described using Independent Suture Tape Reinforcement with 2-year follow-up results. Methods Forty-two consecutive patients with an acute ACL rupture undergoing repair using this technique were followed up for a minimum of 2 years. Patients with mid-substance, distal ACL ruptures, poor ACL tissue quality or retracted ACL remnants as well as patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 29 publications
3
105
1
4
Order By: Relevance
“…These studies also highlight that the DIS Ligamys technique was associated with a high rate of complications, and this may explain the significant deterioration in results. Heusdens et al 47 also reported a deterioration in outcomes following ACL repair with internal bracing, but this finding was not significant. The authors reported that at 12 months postoperatively all components of the Knee injury and Osteoarthritis Outcome Score, VR-12, and visual analog scale for pain showed a significant improvement compared with preoperative scores but that they deteriorated between 12 and 24 months.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These studies also highlight that the DIS Ligamys technique was associated with a high rate of complications, and this may explain the significant deterioration in results. Heusdens et al 47 also reported a deterioration in outcomes following ACL repair with internal bracing, but this finding was not significant. The authors reported that at 12 months postoperatively all components of the Knee injury and Osteoarthritis Outcome Score, VR-12, and visual analog scale for pain showed a significant improvement compared with preoperative scores but that they deteriorated between 12 and 24 months.…”
Section: Discussionmentioning
confidence: 94%
“…The remaining 14 studies were Level IV cases series. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] The flowchart for the search strategy is depicted in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations